Harmonisasi Hukum Administrasi Negara Dengan Konstitusi Dalam Sistim Pemerintahan Di Indonesia - Doni Eka Putra; Sri Agustini; Miasiratni Miasiratni; Gokma Toni Parlindungan S (Universitas Sumatera Barat, 2025)
This journal discusses the Harmonization of State Administrative Law with the Constitution in the Government system in Indonesia. The purpose of the study is to analyze the extent to which State Administrative Law is in line with the values ​​contained in the constitution and how its implementation can strengthen an effective, transparent, and accountable government system. The research method used is a normative legal approach with qualitative analysis, which examines laws and regulations, legal doctrines, and related court decisions. The results of the study indicate that although state administrative law has accommodated constitutional principles, such as justice, legal certainty, and protection of human rights, there are still gaps in implementation. This is due to inconsistencies in regulations, overlapping authority between institutions, and lack of supervision in government administration practices. Therefore, harmonization steps are needed that involve revising regulations, strengthening institutions, and fostering state apparatus to ensure that state administrative law can optimally support the goals of the constitution.